PROBLEMATIQUE DE LA DESSERTE EN ENERGIE ELECTRIQUE A TRAVERS LA VILLE DE KINDU DE 2009 A 2018 - NDJADI LODI Charles, (IJRDO - Journal of Business Management, 2020)
This research has like principal objective, the explanation of the deficit noted through the town of Kindu in electric supply of power coming from the Hydroelectric power station of Rutshurukuru.¶Thus, we supposed that the production and internal consumption justify this deficit.¶Data analysis and processing collected by the method of least squares ordinary, we noted that, during the period appointed for this research:¶-     the production of electrical energy produced by this power station knew a downward trend. ¶The same tendency is observed for consumption with Kindu. ¶On the other hand, internal consumption evolved/moved with the rise.¶-           the model of linear regression multiple estimated reveals that, the deficit in supply of the electric power noted with Kindu is justified by variation with the fall of the production and the variation raises internal consumption.